2022
DOI: 10.1093/mnras/stac599
|View full text |Cite
|
Sign up to set email alerts
|

B/PS bulges in DESI Legacy edge-on galaxies – I. Sample building

Abstract: We present the biggest up-to-date sample of edge-on galaxies with B/PS bulges and X-structures. The sample was prepared using images from the DESI Legacy catalogue and contains about 2000 galaxies. To find suitable candidates in catalogue, we made the assumption that the residues (original images minus model) of galaxies with B/PS bulges should exhibit a characteristic X-shape. Galaxies with such features were selected by eye and then used as input data for a neural network training, which was applied to a big… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 77 publications
2
7
0
Order By: Relevance
“…As part of our analysis, we classify a subsample of bars in an inclination-and bar-position-angle-limited subsample (B/P-Detection Subsample) into those with and without B/P bulges inside their bars. In line with previous work (Erwin & Debattista 2017;Li et al 2017;Marchuk et al 2022), we find a very strong dependence of B/P presence on galaxy stellar mass (or, equivalently, gas rotation velocity Vrot); this dependence is even stronger than found for the smaller sample of Erwin & Debattista (2017), possibly because we use a more consistent set of stellar mass estimates in this paper.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As part of our analysis, we classify a subsample of bars in an inclination-and bar-position-angle-limited subsample (B/P-Detection Subsample) into those with and without B/P bulges inside their bars. In line with previous work (Erwin & Debattista 2017;Li et al 2017;Marchuk et al 2022), we find a very strong dependence of B/P presence on galaxy stellar mass (or, equivalently, gas rotation velocity Vrot); this dependence is even stronger than found for the smaller sample of Erwin & Debattista (2017), possibly because we use a more consistent set of stellar mass estimates in this paper.…”
Section: Discussionsupporting
confidence: 91%
“…Kruk et al (2019) found the same trend using SDSS images for z ∼ 0 barred galaxies, and hints that the trend might be present in higher-redshift galaxies. More recently, Marchuk et al (2022) found a very similar result for B/P bulges identified in edge-on galaxies.…”
Section: Determining the Frequency Of B/p Bulges As A Function Of Gal...supporting
confidence: 57%
See 1 more Smart Citation
“…If the galaxies of interest are well restricted in terms of their light distribution or overall shape they can be selected based on their internal parameters, for instance Gini coefficient (G) and M20 index are known to be a good indicator of galaxy's morphology (Lotz, Primack, & Madau 2004) while axial ratio is a good tool to select edge-on galaxies (Mitronova et al 2004;Bizyaev et al 2014). With the ever increasing computational capacity of modern processors it is now possible to employ computer vision techniques with explicit algorithms (Timmis & Shamir 2017) or machine learning methods (Yi et al 2022;Marchuk et al 2022;Makarov et al 2022;Vavilova et al 2021;Cheng et al 2020). Although ML is a very powerful tool that proved itself in a plethora of scenarios this technique has its own limitations, namely, a requirement of a relatively large representative training sample.…”
Section: Samples Of Galaxiesmentioning
confidence: 99%
“…Attention has been devoted to identifying and cataloguing these systems (e.g. Mitronova et al 2004;Bizyaev et al 2014;Makarov & Antipova 2021;Marchuk et al 2022). High-resolution infrared imaging will soon be available with the James Webb Space Telescope which will help explore current edge-on B/P samples across cosmic time.…”
Section: Future Prospectsmentioning
confidence: 99%